Isolated thrombosis of the vein of Labbe after contralateral cortical subarachnoid hemorrhage of unknown origin with positive antinuclear antibody. Issue 3 (29th May 2014) - Tabuchi, Sadaharu; Ishii, Takashi; Nakayasu, Hiroyuki; Watanabe, Takashi
Abstract We report a rare case of isolated thrombosis of the vein of Labbe after subarachnoid hemorrhage (SAH) of unknown origin on the contralateral side. A 39‐year‐old man with no known previous medical history suffered from headaches and nausea. Computed tomography showed a mild SAH in the right distal Sylvian fissure. Digital subtraction angiography (DSA) showed no vascular lesion responsible for the SAH. Six days after admission, he suddenly developed generalized seizures. Computed tomography showed a high‐density lesion in the left temporal lobe. Magnetic resonance imaging showed the pattern of hemorrhagic infarction. DSA showed a complete filling defect of the left vein of Labbe. Anticoagulation and anticonvulsant treatment were carried out. The clinical course was favorable. After discharge, laboratory examinations showed remarkably increased antinuclear antibody titer (×2560). Although the antiphospholipid syndrome was denied, the high level of antinuclear antibody might have been related to these lesions through an unknown etiology.